Photoaffinity labelling of a nitrobenzylthioinosine-binding polypeptide from cultured Novikoff hepatoma cells. - Gati, W P (1986)
Site-specific binding of nitrobenzylthioinosine (NBMPR) to plasma membranes of some animal cells results in the inhibition of the facilitated diffusion of nucleosides. The present study showed that nucleoside transport in Novikoff UA rat hepatoma cells is insensitive to site-saturating concentrations of NBMPR. Equilibrium binding experiments demonstrated the presence of high-affinity sites for NBMPR in a membrane-enriched fraction from these cells. In the presence of uridine or dipyridamole, specific binding of NBMPR at these sites was inhibited. When Novikoff UA membranes were covalently labelled with [3H]NBMPR by using photoaffinity techniques, specifically bound radioactivity was incorporated exclusively into a polypeptide(s) with an apparent Mr of 72,000-80,000, determined by sodium dodecyl sulphate/polyacrylamide-gel electrophoresis. Covalent labelling of this polypeptide was abolished in the presence of excess nitrobenzylthioguanosine (NBTGR) and reduced in the presence of adenosine, uridine or dipyridamole. The apparent Mr of the NBMPR-binding polypeptide in Novikoff UA cells is significantly higher than that reported for corresponding polypeptides in other cell types (Mr 45,000-66,000). When membrane-enriched preparations from S49 mouse lymphoma cells were photolabelled and mixed with labelled NovikoffUA membrane-enriched preparations, gel electrophoresis resolved the NBMPR-binding polypeptides from the two preparations.